A comparative study on port-site infection following gall bladder retrieval using endobag and conventional method in laparoscopic cholecystectomy - Jemin Bharath R; Renganathan M; Mukesh Kumar P; Ganesh Kumar C; Sathyaraj P (Asian Journal of Medical Sciences, 2023)
Background: Gallbladder (GB) retrieval is essential to reduce postoperative pain after laparoscopic cholecystectomy (LC). Limited data are available for the use of endobags for GB extraction. Aims and Objectives: The study aims to assess the incidence of postoperative infection after GB extraction. Materials and Methods: The randomized prospective study was conducted in the Department of General Surgery, Government Rajaji Hospital, for 6 months. After the ethical approval, 100 patients who underwent elective LC were enrolled in the study. Patients who underwent LC and removed the GB using an endobag were included in Group A. The patients in whom the bladder was removed without using an endobag were included in Group B. Results: The study reports a female predominance, 76% in Group A and 70% in Group B. A significant difference was reported between the port-site spill in Group B patients who underwent conventional treatment without endobags and reported spillage in six patients (12.0%). In addition, port-site infection was also prevalent in four patients under Group B with a significant difference, respectively. The mean operating time was higher in Group A patients with 88.24±7.4 (hours) compared with Group B with 85.3±6.6 (hours); however, no significant difference was reported between operating time and hospital stay. Conclusion: The use of endobags in GB extraction has been reported beneficial with a lower incidence of port-site spillage and infection. This signifies the essential benefit of endobags for GB extraction with a lower incidence of postoperative complications.